ANALYSIS OF THE USE OF GOOGLE CLASSROOM ON PROTISTA MATERIALS IN 10th GRADE SCIENCE CLASS - Widya Arwita; Lita Ayu Ningrum (Jurnal Pelita Pendidikan, 2022)
This research aims to describe students' understanding of the use of Google Classroom for learning protist material in class X SMA Negeri 1 Bilah Hulu in the odd semester of the 2021-2022 academic year and to determine student learning outcomes while using Google Classroom on Protista material in class X SMA Negeri 1 Bilah Hulu semester odd for the 2021-2022 school year. The research method used is descriptive quantitative. The sampling technique is purposive sampling. The purposive sampling technique in this study is seen in students' activeness in class. The results of this study indicate that class X MIA 1 and X MIA 2 obtained an average score and score on the questionnaire using Google Classroom, which is a score of 3.8 with a value of 77, which is in the understanding category but requires a slight improvement, this is because students still need to understand the features of using Google Classroom.